Amyloid beta plaque reduction with antibodies crossing the blood brain barrier opened with focused ultrasound in a rabbit model - Yiannakou, Marinos; Damianou, Christakis A. (My University, 2015)
The main objective of the study was to treat Alzheimer's disease (AD) plaques using focused ultrasound (FUS) induced blood brain barrier (BBB) opening with and without delivery of antibodies in a rabbit model for AD. The animal model was achieved by feeding a high cholesterol diet to rabbits for 4 months. A single spherically focused MRI compatible transducer was used which operated at 1 MHz, had a focal length of 10 cm and diameter of 4 cm. By increasing the number of sessions, the number of plaques decreased (both for antibodies, and without antibodies). This study demonstrated that by opening the BBB, it will be possible to deliver exogenous antibodies to the brain, which eliminates Amyloid β plaques.
Keywords: Alzheimer; Amyloid betaplaque; Αntibody; Βrain; Focused ultrasound; MRI